Pathogenic effects of agrin V1727F mutation are isoform specific and decrease its expression and affinity for HSPGs and LRP4 - Rudell, John B (Hum Mol Genet, 2019)
Agrin is a large extracellular matrix protein whose isoforms differ in their tissue distribution and function. Motoneuron-derived y+z+ agrin regulates the formation of the neuromuscular junction (NMJ), while y−z− agrin is widely expressed and has diverse functions. Previously we identified a missense mutation (V1727F) in the second laminin globular (LG2) domain of agrin that causes severe congenital myasthenic syndrome. Here, we define pathogenic effects of the agrin V1727F mutation that account for the profound dysfunction of the NMJ. First, by expressing agrin variants in heterologous cells, we show that the V1727F mutation reduces the secretion of y+z+ agrin compared to wild type, whereas it has no effect on the secretion of y−z− agrin. Second, we find that the V1727F mutation significantly impairs binding of y+z+ agrin to both heparin and the low-density lipoprotein receptor-related protein 4 (LRP4) coreceptor. Third, molecular modeling of the LG2 domain suggests that the V1727F mutation primarily disrupts the y splice insert, and consistent with this we find that it partially occludes the contribution of the y splice insert to agrin binding to heparin and LRP4. Together, these findings identify several pathogenic effects of the V1727F mutation that reduce its expression and ability to bind heparan sulfate proteoglycan and LRP4 coreceptors involved in the muscle-specific kinase signaling pathway. These defects primarily impair the function of neural y+z+ agrin and combine to cause a severe CMS phenotype, whereas y−z− agrin function in other tissues appears preserved.